HUBUNGAN PENGETAHUAN, SIKAP, DUKUNGAN SUAMI DENGAN KESIAPAN WANITA MENGHADAPI MENOPAUSE DI RW 08 CIBEBER CIMAHI SELATAN - Damai Yanti (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2021)
Background, in Indonesia most women experience menopause around the age of 50 years, and in some women menopause can take place at around 40 years of age or no later than 60 years (Soehartono, 2010). Until the end of the 21st century there were around 18,000,000-20,000,000 elderly, which is a significant number and requires serious attention. In Indonesia, it is the responsibility of the elderly to take care of them. The purpose of this study was to find out how the relationship between husband support and women's readiness to face menopause. The method used in this study was an analytical survey. The measurement design is carried out in a cross-sectional manner, namely a research design by measuring or observing at the same time (one time). The research was conducted at RW 8 Cibeber, South Cimahi. The study was conducted in January - August 2020. The population in this study were all mothers aged 45-59 years who lived in RW 8 Cibeber, Cimahi Selatan, totaling 163 people. Results of the analysis of the relationship between husband's support and readiness, there were 28 (44%) of 40 people whose husband's support was not supported with readiness in the unprepared category, while 7 (11%) of 23 people whose readiness were in the unprepared category. The results of the Chi-square test obtained a p value of 0.003, which means that there is a significant relationship between husband's support and women's readiness to face menopause. The conclusion in this study is that women's knowledge about menopause has a significant relationship with women's readiness to face menopause. The attitude of women about menopause has a significant relationship with women's readiness to face menopause. Husband's support for menopause has a significant relationship with women's readiness to face menopause.